International law : cases and materials with Australian perspectives - Rothwell, Donald, 1959-; Kaye, Stuart B.; Akhtarkhavari, Afshin; Davis, Ruth, (Ruth Amanda); Saunders, Imogen (Australia : Cambridge University Press, 2018)
'Now in its third edition, International Law: Cases and Materials with Australian Perspectives remains an authoritative textbook on international law for Australian students. With a strong focus on Australian practice and interpretation, the text examines how international law is developed, implemented and interpreted within the international community and considers new and developing approaches within this field. This edition has been comprehensively updated to address recent developments in international law. The selection of cases and materials provides a thorough coverage of core areas and addresses a range of contemporary challenges, including climate change, human rights, nuclear proliferation and the South China Sea. A new chapter on international trade law reflects the growing importance of this body of law in Australian practice. Guiding commentary provides a rigorous analysis of key principles. Written by a team of experts with substantial experience in this field, International Law is an essential resource for students.'--Publisher's description.
The nature of international law -- Sources of international law -- Law of treaties -- International and municipal law -- International legal personality -- Sovereignty over territory -- Jurisdiction -- State responsibility -- Human rights -- Law of the sea -- International environmental law -- International trade law -- Use of force -- Enforcement of international law -- The peaceful settlement of international disputes.
Includes bibliographical references and index.
Keywords: International law; International law -- Australia